Post deposition annealing effect on properties of Y2O3/Al2O3 stacking gate dielectric on 4H-SiC - Zhao, Feng; Amnuayphol, Oliver; Cheong, Kuan Yew; Wong, Yew Hoong; Jiang, Jheng-Yi; Huang, Chih-Fang (Elsevier, 2019)
In this paper, the effect of post deposition annealing (PDA) on the chemical, structural, and electrical properties of the high-k Y 2 O 3 /Al 2 O 3 stacking dielectric on p-type 4H-SiC were studied. High-k dielectric provides a physically thicker film with equivalent capacitance, therefore better exploits the high breakdown strength of 4H-SiC in its MOSFET devices. The Y 2 O 3 /Al 2 O 3 stacking films were deposited using RF magnetron sputtering, with PDA in Ar ambient at 400 °C, 600 °C, 800 °C and 1000 °C. X-ray diffraction (XRD) and angle resolved X-ray photoelectron spectroscopy (XPS) results show that an Al 5 O 12 Y 3 crystal layer was formed in between Y 2 O 3 and Al 2 O 3 films after annealing above 600 °C. High resolution transmission electron microscope (HRTEM) was used to investigate the atomic structure and measure the thickness of each layer. Charges and dielectric strength of the stacking films were characterized by high frequency capacitance-voltage (C-V) and current-voltage (I-V) measurements. The lower charge density and higher dielectric strength were found after PDA at 800 °C and 1000 °C.